Does "altitude training" increase exercise performance in elite athletes? - Lundby, Carsten; Bärtsch, Peter (British journal of sports medicine, 2012)
The general practice of altitude training is widely accepted as a means to enhance sport performance despite a lack of rigorous scientific studies. For example, the scientific gold-standard design of a double-blind, placebo-controlled, cross-over trial has never been conducted on altitude training. Given that few studies have utilised appropriate controls, there should be more scepticism concerning the effects of altitude training methodologies. In this brief review we aim to point out weaknesses in theories and methodologies of the various altitude training paradigms and to highlight the few well-designed studies to give athletes, coaches and sports medicine professionals the current scientific state of knowledge on common forms of altitude training. Another aim is to encourage investigators to design well-controlled studies that will enhance our understanding of the mechanisms and potential benefits of altitude training.
Published online first 14 July 2012
Gesehen am 25.06.2018